Application of Geo-information Technology in Nepal “During and Post” COVID -19 (Journal on Geoinformatics, Nepal, 2020)
At present, the world is facing the challenges to combat the pandemic situation due to outbreak of COVID-19. There is a global realization that the effects of COVID-19 will be in long term affecting various sectors of social and economic development. To support this health crisis, along with various non-pharmaceutical interventions (NPI) the application of geo-information technology have proven to be significant for delaying and containing the COVID-19 pandemic. The application of geo-information technology is one of the interventions adopted basically in the monitoring of the COVID-19 cases. This paper attempt to shade a light on the present scenario in the use of geo-information technology in Nepal and has attempted to throw lights on the need of wider application of such technologies to combat Post COVID-19 crisis. Further, the academic program like geomatics engineering currently running at Kathmandu University can be a contributor of technical human resources and can provide academic research output necessary for strengthening the domain of geo-information technology in the settings of Post Pandemic context.